The graveyard book. Volume 1 - Russell, P. Craig (Harper, 2014)
Presents a graphic adaptation of the life of Nobody Owens who is raised in a graveyard by a group of ghosts and avoids leaving the graveyard for fear that he will be killed by the man who has already murdered his family.